2022
DOI: 10.1371/journal.ppat.1010596
|View full text |Cite
|
Sign up to set email alerts
|

Excessive immunosuppression by regulatory T cells antagonizes T cell response to schistosome infection in PD-1-deficient mice

Abstract: Schistosomiasis is caused by parasitic flatworms known as schistosomes and affects over 200 million people worldwide. Prevention of T cell exhaustion by blockade of PD-1 results in clinical benefits to cancer patients and clearance of viral infections, however it remains largely unknown whether loss of PD-1 could prevent or cure schistosomiasis in susceptible mice. In this study, we found that S. japonicum infection dramatically induced PD-1 expression in T cells of the liver where the parasites chronically in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Granulocytic myeloid‐derived suppressor cells might regulate Tfh cells through the PD‐1/PD‐L1 pathway 15 . A recent study has shown that PD‐1‐deficient Tregs expressed larger amounts of adenosine receptors CD39 and CD73 that were crucial for Treg‐mediated immunosuppression 16 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granulocytic myeloid‐derived suppressor cells might regulate Tfh cells through the PD‐1/PD‐L1 pathway 15 . A recent study has shown that PD‐1‐deficient Tregs expressed larger amounts of adenosine receptors CD39 and CD73 that were crucial for Treg‐mediated immunosuppression 16 …”
Section: Introductionmentioning
confidence: 99%
“…15 A recent study has shown that PD-1-deficient Tregs expressed larger amounts of adenosine receptors CD39 and CD73 that were crucial for Tregmediated immunosuppression. 16 Sj16 was first identified from S. japonicum as a homolog of Sm16 from S. mansoni, 17 and was reported to be upregulated in the parasite stages of cercariae, eggs, miracidia, sporocysts, and lung-stage schistosomula. 18 The recombinant protein Sj16 (rSj16) has anti-inflammatory effects both in vivo and in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study found that liver CD4+ T cells, CD8+ T cells, NK1.1+ cells, and CD11b+ cells have increased TIM-3 expression during S. japonicum infection, and antibody-mediated blockade of TIM-3 on CD11b+ cells (from infected mice) co-cultured with soluble egg antigen (SEA) resulted in the upregulation of the classically activated (M1) macrophage-associated markers Nos2 (iNOS synthase) and Il12 and the downregulation of M2 macrophage-associated markers Arg1 (liver arginase) and Il10 [73]. A study examining PD-1 in the context of schistosome infection (reviewed in [74]) found an increase in PD-1 expression in the liver of S. japonicum -infected mice and that infected PD-1- deficient (versus infected wild-type) mice have a decreased population of cells that express IL-4 and IL-13 and an increased population of cells that express IFNG and FOXP3 [75], suggesting that PD-1 signaling supports a type 2 immune phenotype. Studies on PD-1 binding partners PD- L1 and PD-L2 found that splenic F4/80+ macrophages from mice infected with S. mansoni express elevated levels of PD-L1 and can induce anergy in T cells in a PD-L1-dependent manner [76], and that S. japonicum SEA can induce PD-L2 expression on bone marrow-derived dendritic cells (BMDCs) in a TLR2-dependent manner [77], suggesting that schistosome infection can alter PD-L1 and PD-L2 signaling to suppress T cell responses.…”
Section: Discussionmentioning
confidence: 99%
“…Such an immune bias by PD-1 stimulation was not observed in studies using gene-deficient mice. Mice lacking PD-1 or PD-L1 indicated highly active Th1-type immune response in Leishmaniasis (29) and Schistosomiasis (30). Associated with the enhanced Th1 immunity, PD-1-knockout mice have shown intense CD8 + T cell-dependent proinflammatory activities in anti-tumor response (31)(32)(33) and in contact hypersensitivity (34,35).…”
Section: Discussionmentioning
confidence: 99%